2020
DOI: 10.1161/circinterventions.119.008372
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Valvulo-Arterial Impedance on Long-Term Quality of Life and Exercise Performance After Transcatheter Aortic Valve Replacement

Abstract: BACKGROUND:In aortic stenosis, valvulo-arterial impedance (Zva) estimates the overall left ventricular afterload (valve and arterial component). We investigated the association of Zva (≥5 versus <5 mm Hg mL −1 m −2 ) on quality of life (QOL) and exercise performance (EP) ≥1 year after transcatheter aortic valve replacement (TAVR). METHODS:The study population consists of 250 TAVR patients in whom baseline Zva and follow-up QOL was prospectively assessed using EuroQOL-5-dimensions instruments; EP was assessed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…The use of arterial biomarkers and indices that encompass and take into account the effect of as many pathophysiological aspects can prove crucial in the assessment of true hemodynamic severity of AVS in cases that traditional indices seem to be insufficient. For example, in patients with paradoxical low-flow, lowgradient severe AVS, the estimation of Zva (which is a surrogate measure of global LV afterload that incorporates both the valvular and the vascular component) might be useful, especially when Zva is > 5 mmHg/mL/m 2 , for the clinician to unmask the pseudonormalization of gradient and blood pressure [40,57]. Moreover, increased aortic stiffness could identify patients that are prone to develop paradoxical low-flow, low-gradient subtypes during the progression of AVS independently of echocardiographic severity indices.…”
Section: True Hemodynamic Loadmentioning
confidence: 99%
“…The use of arterial biomarkers and indices that encompass and take into account the effect of as many pathophysiological aspects can prove crucial in the assessment of true hemodynamic severity of AVS in cases that traditional indices seem to be insufficient. For example, in patients with paradoxical low-flow, lowgradient severe AVS, the estimation of Zva (which is a surrogate measure of global LV afterload that incorporates both the valvular and the vascular component) might be useful, especially when Zva is > 5 mmHg/mL/m 2 , for the clinician to unmask the pseudonormalization of gradient and blood pressure [40,57]. Moreover, increased aortic stiffness could identify patients that are prone to develop paradoxical low-flow, low-gradient subtypes during the progression of AVS independently of echocardiographic severity indices.…”
Section: True Hemodynamic Loadmentioning
confidence: 99%
“…Back in 2009, the concept of valvulo-arterial impedance was introduced by Hachicha et al, and this parameter was shown to be independently associated with mortality in aortic stenosis patients who underwent either surgical aortic valve replacement or medical therapy (28). After that, valvulo-arterial impedance was evaluated in multiple studies as a post-TAVR outcome predictor (10,(14)(15)(16)29,30). A cohort study containing 202 TAVR patients reported that patients who died within 6 months had higher baseline Zva and less improvement in post-TAVR Zva.…”
Section: Valvulo-arterial Impedance: a Close Shotmentioning
confidence: 99%
“…Given the underlying comorbidities, the clinical outcomes after TAVR procedure have gained significant attention that involves both conventional and machine learning research approaches (5)(6)(7)(8)(9)(10)(11)(12). There are newer studies focused on the relationship of blood pressure and valvuloarterial impedance (Zva), which estimates the overall left ventricular afterload, and its effect on TAVR prognosis (8)(9)(10)13). Elevated Zva has been reported to be associated with worse quality of life and exercise performance at one year (10), while there are inconsistent results in predicting long-term mortality (14)(15)(16).…”
Section: Background/introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that the LV global afterload (Zva) was a main predictor of lower stress-corrected mid wall shortening, independent from LV geometry, hypertrophy, and hypertension, despite of mean LVEF all at 60% [82]. In TAVI patients, Nuis et al [83] reported an elevated Z-va occurred in half of the patients at base line and reduced to 21% at 1 year after TAVI, but the patients who had remained to have elevated Z-va were associated with poor quality of life and exercise performance.…”
Section: Effects Of Pacemaker and Bundle Branch Block On LV Remodelling And Outcomementioning
confidence: 99%